Analisis Plagiarisme Lukisan Digital Melalui Instagram Ditinjau Menurut Undang-Undang Hak Cipta - Sava Waroha Sasikirana Haq; Yudho Taruno Muryanto (CV. ITTC INDONESIA, 2025)
This research aims to identify criteria for plagiarism in digital painting artworks posted on Instagram based on Law No. 28 of 2014 concerning Copyright in order to create legal certainty and prevent errors in interpretation and application of legal protection. This study employs normative legal research that is prescriptive and applied, using a legislative and conceptual approach. The legal materials used are primary and secondary legal sources, with legal data collection techniques involving literature review analyzed using deductive syllogistic methods. Based on this research, the results obtained are that the criteria for plagiarism of digital painting artworks through Instagram are: a) the use, taking, reproduction, and/or modification of a work, b) failure to mention or fully cite the source, thereby implying recognition of the work, c) lack of permission from the creator or copyright holder, and d) objections from the creator or copyright holder. The identification of these plagiarism criteria can assist in determining legal protection for creators within relevant legal frameworks and application policies, including preventive measures such as registration of works and monitoring, as well as repressive measures such as reporting copyright infringements, restrictions, closures, or content removal, and resolving disputes through non-litigation or litigation channels, accompanied by shared legal awareness among all parties.